Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1103/physrevb.71.125404
|View full text |Cite
|
Sign up to set email alerts
|

Pressure screening in the interior of primary shells in double-wall carbon nanotubes

Abstract: The pressure response of double-wall carbon nanotubes has been investigated by means of Raman spectroscopy up to 10 GPa. The intensity of the radial breathing modes of the outer tubes decreases rapidly but remain observable up to 9 GPa, exhibiting a behavior similar (but less pronounced) to that of single-wall carbon nanotubes, which undergo a shape distortion at higher pressures. In addition, the tangential band of the external tubes broadens and decreases in amplitude. The corresponding Raman features of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
82
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 25 publications
16
82
1
Order By: Relevance
“…Flattening of the tubes is a transition observed for a large diameter range 45 and is predicted 50 to vary as 1/d 3 . For DWCNTs 15,16 several calculations have shown a small reinforcement of the tube and a transition to the elliptical shape as is observed for SWCNTs (Table 1). Several reports consider ordered layers of the medium on the CNT surface to explain the presence of plateaus or the slope vs the pressure curve.…”
Section: Summary Of Pressure-and Temperature-induced Effects Of the Dmentioning
confidence: 98%
See 1 more Smart Citation
“…Flattening of the tubes is a transition observed for a large diameter range 45 and is predicted 50 to vary as 1/d 3 . For DWCNTs 15,16 several calculations have shown a small reinforcement of the tube and a transition to the elliptical shape as is observed for SWCNTs (Table 1). Several reports consider ordered layers of the medium on the CNT surface to explain the presence of plateaus or the slope vs the pressure curve.…”
Section: Summary Of Pressure-and Temperature-induced Effects Of the Dmentioning
confidence: 98%
“…13 Inter-layer coupling between the two walls in DWCNTs has been investigated for RBMs using resonant Raman scattering. 14 Hydrostatic pressure experiments on DWCNT's 15,16 show that the G band splits with pressure. The wavenumber at zero pressure of the inner tube is close to 1582 cm 1 while the wavenumber of the outer tube is close to 1592 cm 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The internal wall experiences a smaller stress due to shielding by the external wall. 5,6 Effects due to the pressure transmitting medium, in hydrostatic experiments, have been reported earlier and evaluation of hydrostatic pressure condition remains controversial. The broadening of the observed luminescence line ͑R1͒ of ruby crystals in the pressure medium is usually used to evaluate the deviation from hydrostatic pressure condition.…”
mentioning
confidence: 99%
“…10,11 The methanol-ethanol medium is used in several high pressure studies on CNTs. 6,[12][13][14][15][16][17] Argon gas adsorption studies on CNTs 18 identified several adsorption sites: interstitial channels, external groove sites, and the external surface. Pseudohexagonal medium range ordering of adsorbents have been predicted on the external surface of CNTs.…”
mentioning
confidence: 99%
“…The G band of agglomerated DWCNTs is composed of three components, one around 1550 cm −1 denoted as high energetic mode ͑HEM͒, and two at 1580 cm −1 which split with increasing hydrostatic pressure. 9,10 The one-dimensional structure of CNTs leads to singularities in the electronic density of states ͑Van Hove singularities͒. This has the effect that the absorption of CNTs is particularly strong when the excitation wavelength corresponds to one of the transition energies between two corresponding singularities in the electronic states.…”
mentioning
confidence: 99%